Time courses of strains that induce necking and fracturing in high-density polyethylene - Hao, S.; Wu, X.; Lu, Chunsheng (2023)
High-density polyethylene is widely used in pressure pipe applications, but its necking and pre-cut effects are still poorly understood. Herein, we analyze the spatial distributions of the time courses of strains to highlight the strain field evolution to necking and the effect of pre-cutting on the strain field evolution in a high-density polyethylene material deformed under tension. Digital image correlation was used to measure the strain fields on two perpendicular surfaces of a specimen. Necking and its propagation in the tension direction dominate the failure behavior of an intact specimen. However, in the pre-cut specimen, crack propagation prevents neck propagation in the tension direction. Energy release outside the crack zone is observed as a decrease in strain at approximately the failure time. This leads to a macroscopic stress-strain curve that deviates from that of the intact specimen. These findings provide novel insights that are significant in the theoretical modelling and simulations of advanced polymeric materials and structures.